PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN GAMIFIKASI TERINTEGRASI EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) TERHADAP HASIL BELAJAR MATA PEMBELAJARAN BIOLOGI SISWA KELAS X PADA MATERI EKOSISTEM DI MA MA’ARIF NU KENCONG TAHUN PEMBELAJARAN 2025/2026 - Naura Widadur Rohmah; Abdillah Fatkhul Wahab (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low utilization of innovative learning media and limited teacher understanding of the Education for Sustainable Development (ESD) approach have contributed to students’ low learning outcomes in ecosystem material. This study aimed to determine the effect of ESD-integrated gamification learning media on the biology learning outcomes of tenth-grade students at MA Ma’arif NU Kencong in the 2025/2026 academic year. This study used a quantitative approach with a Pre-Experimental Design through a One-Group Pretest-Posttest design. The sample consisted of 30 students selected using a saturated sampling technique. Data were collected through multiple-choice pretest and posttest on biogeochemical cycle material. Data analysis used the Shapiro-Wilk normality test, homogeneity test, and paired sample t-test assisted by IBM SPSS version 31. The results showed that the data were normally distributed with significance values of 0.204 for the pretest and 0.795 for the posttest, and had homogeneous variance with a significance value of 0.522. The paired sample t-test showed a Sig. (2-tailed) value of 0.000 < 0.05 with a mean difference of -4.90, indicating a significant improvement in students’ learning outcomes after the implementation of ESD-integrated gamification learning media. Therefore, it can be concluded that ESD-integrated gamification learning media significantly affect students’ biology learning outcomes on ecosystem material.